PENGARUH MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF TERHADAP HASIL BELAJAR TEMA 7 SUBTEMA 2 DI KELAS IV SD N 101767 TEMBUNG - Eva Betty Simanjuntak; Sri Mustika Aulia; Krystika Simamora (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This study aims to determine the effect of interactive multimedia-based learning media on Theme 7 Subtema 2 class IV SDN 101767 Tembung. This research is an experimental research with quasi-experimental technique. The sample in this study was class IVA SDN 101767 Tembung which amounted to 20 students. From the analysis of the data obtained the results of the average pre-test (53) while the post-test (67, 8) at a significant level (α = 0, 05), the normal results of the pre-test were obtained L0 <Ltable (0, 1301 <2 , 1242) so that it can be concluded that the data are Normal Distributed. Likewise, the results obtained in the post-test are L0 <Ltable (0, 1397 <2, 1242) so that it can be concluded that the data is Normal Distributed. Homogeneity results obtained are Fcount <F table = 0, 58 <2, 97 then the variant is homogeneous. The use of interactive multimedia-based learning media in class IV-A SD Negeri 101767 Tembung in the good category with an average value of 88, 32. T test was carried out at the level (α = 0, 05) tcount> ttable = 4, 36> 2, 09 , so Ha was accepted, namely "There is an Effect of Interactive Multimedia-based Learning Media on Learning Outcomes of Theme 7 Subtheme 2 Class IV Students in SD N 101767 Tembung".Keywords: Learning Outcomes, Media, Interactive Multimedia